Perancangan User Experience Pada Aplikasi Pencarian Car Wash Menggunakan Metode UCD (User Centered Design): English - Tiara Andhiza; Iskandar Fitri; Albaar Rubhasy (SMATIKA JURNAL : STIKI Informatika Jurnal, 2022)
The high level of busyness in urban areas makes efficiency in using time important. The need to wash a car is often constrained by a little free time. Based on this, the application system design for finding the nearest car wash application quickly and easily was built, so that it can help users save time. The method that will be used in the process of making this application system is using a user centered design. This Speed Wash application system can be used for all circles, especially drivers to get information on car washes based on location, price, rating, and the type of service available on the car wash.